2008
DOI: 10.1108/17542410810878086
|View full text |Cite
|
Sign up to set email alerts
|

Still a man's world

Abstract: PurposeAlthough qualified women are entering professional and managerial ranks within organizations, they continue to have difficulties in advancing their careers. It has been suggested that the biggest obstacle to women's career advancement lies in the attitudes, biases and prejudices of their male colleagues and their organizational cultures. The purpose of this paper is to examine the relationship of perceptions of organizational bias among managerial and professional women and their work satisfactions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 25 publications
(22 reference statements)
0
8
1
Order By: Relevance
“…Hypothesis 1 states that gender moderates the prediction of turnover intentions. The current study's findings, however, do not support Hypothesis 1 and subsequently contradict the findings of previous studies (Almer & Kaplan, 2002;Burke, Koyuncu, & Fiksenbaum, 2008;Cotton & Tuttle, 1986;Coyne & Ong, 2007;Harris, Andrews & Kacmar, 2007;Karatepe & Aleshinloye, 2009;Zhen & Francesco, 2000) that reported moderation effects of gender in predicting TIs. This result is unexpected, and cannot be easily explained.…”
Section: Summary Of Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Hypothesis 1 states that gender moderates the prediction of turnover intentions. The current study's findings, however, do not support Hypothesis 1 and subsequently contradict the findings of previous studies (Almer & Kaplan, 2002;Burke, Koyuncu, & Fiksenbaum, 2008;Cotton & Tuttle, 1986;Coyne & Ong, 2007;Harris, Andrews & Kacmar, 2007;Karatepe & Aleshinloye, 2009;Zhen & Francesco, 2000) that reported moderation effects of gender in predicting TIs. This result is unexpected, and cannot be easily explained.…”
Section: Summary Of Resultscontrasting
confidence: 99%
“…Despite the fact that men and women share similar psychological structures and developmental processes during identity formation (Kroger, 1997), their spheres of work differ and are not rated as equal (Béteille, 2002). Several studies support moderator effects of gender in the prediction of TI (Almer & Kaplan, 2002;Burke, Koyuncu & Fiksenbaum, 2008;Cotton & Tuttle, 1986;Coyne & Ong, 2007;Harris, Andrews & Kacmar, 2007;Karatepe & Aleshinloye, 2009;Zhen & Francesco, 2000). Men reported higher levels of depersonalisation than women (Almer & Kaplan, 2002), resulting in the first research hypothesis to be tested.…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…Scholars have studied career-related variables and engagement as separate outcome variables rather than focusing on their causal relationship. Career commitment (Littman-Ovadia, Oren, & Lavy, 2013) and career satisfaction (Burke, Koyuncu, & Fiksenbaum, 2008; Fiksenbaum, Jeng, Koyuncu, & Burke, 2010; Smith et al, 2012) have been explored, with the findings largely consistent with the outcome variables of engagement. In particular, some scholars have viewed career satisfaction, career commitment, and engagement as components of work-related attitudes and emotions (Littman-Ovadia et al, 2013), subjective success (Smith et al, 2012), and work outcomes (Burke et al, 2008).…”
Section: Findings On Work Engagement and Careermentioning
confidence: 75%
“…These include: negative assumptions in executive ranks about women, their abilities, and their commitment to careers; perceptions that women do not fit the corporate culture; lack of career planning and the range of job experiences to fill the future needs of the organization; failure to make managers accountable for developing and advancing women; lack of mentoring and exclusion form informal career networks; and discrimination and sexual harassment, among others (see Burke & Nelson, 2002, for others). Burke, Koyuncu, and Fiksenbaum (2008a), in a study of 215 female managers and professionals working in a large Turkish bank, reported that women indicating greater perceptions of organizational bias favouring men reported less job satisfaction, lower levels of work engagement and more job stress; these perceptions were not related to turnover intention. Perceptions of organizational bias were also related to exhaustion but not self-reported psychosomatic symptoms.…”
mentioning
confidence: 97%